Effect of the Silica Content of Diatoms on Protozoan Grazing - Zhang, Shuwen; Liu, Hongbin; Ke, Ying; Li, Beatrice (Frontiers in Marine Science, 2017)
This study examined the effect that silica content in diatom cells has on the behavior of protists. The diatoms Thalassiosira weissflogii and T. pseudonana were cultured in high or low light conditions to achieve low and high silica contents, respectively. These cells were then fed to a heterotrophic dinoflagellate Noctiluca scintillans and a ciliate Euplotes sp. in single and mixed diet experiments. Our results showed that in general, N. scintillans and Euplotes sp. both preferentially ingested the diatoms with a low silica content rather than those with a high silica content. However, Euplotes sp. seemed to be less influenced by the silica content than was N. scintillans. In the latter case, the clearance and ingestion rate of the low silica diatoms were significantly higher, both in the short (6-h) and long (1-d) duration grazing experiments. Our results also showed that N. scintillans required more time to digest the high silica-containing cells. As the high silica diatoms are harder to digest, this might explain why N. scintillans exhibits a strong preference for the low silica prey. Thus, the presence of high silica diatoms might limit the ability of the dinoflagellate to feed. Our findings suggest that the silica content of diatoms affects their palatability and digestibility and, consequently, the grazing activity and selectivity of protozoan grazers.